Flipping between Polycomb repressed and active transcriptional states introduces noise in gene expression - Gozde Kar (Nature Portfolio, 2017)
Polycomb repressive complexes modify histones but it is unclear how changes in chromatin states alter kinetics of transcription. Here, the authors use single-cell RNAseq and ChIPseq to find that actively transcribed genes with Polycomb marks have greater cell-to-cell variation in expression.